Enhancing Netizen As A Digital Marketing Activity Toward Strategic Branding: A Case Study of “XYZ” Brand - Nila Krisnawati Hidayat; Rudy Tobing (Bina Nusantara University, 2012)
This study is focused on the role of netizen in digital marketing activities to attempt the development of strategic brand of “XYZ”. The purpose of this study to identify whether netizen as users have recognize the “XYZ” brand as a product of internet mobile, through four variables of brand performances: delivery message, creative advertisement, product understanding, and brand association. It is also to measure users’ level of awareness to the website of “murah itu XYZ”. The research methodology applied in this study is descriptive quantitative study using Likert scale. The result shows that the highest level of brand performance is not only from delivery message, but it also indicates that netizen have recognized the “XYZ” as internet mobile under the activity of digital marketing. In addition, users are not aware yet to the website of “murah itu XYZ”. The content of the mobile advertising should be increased in the near future.